Peran Indonesia dan Organisasi Kerja Sama Islam (OKI) dalam Menghadapi Dominasi Negara Maju Atas Pelanggaran HAM pada Konflik Israel–Palestina - Regar Vina Febrina; Muldiana Muldiana; Maria Kristin Ningrum; Ananda Nurul Hidayah; Arifin Eka Putra (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The Israel–Palestine conflict continues to generate widespread human rights violations, yet international responses are often fragmented due to the political dominance of developed nations, raising critical questions about the effectiveness of human rights protection. This study aims to conduct an in-depth analysis of how such dominance, particularly the use of veto power in the UN Security Council and the provision of direct political and military support, it affects the asymmetry of civilian protection and delays the cessation of hostilities. Using a doctrinal method with normative–qualitative analysis of resolutions, official reports, and global justice frameworks, this research also evaluates the effectiveness of normative diplomacy carried out by Indonesia and the Organization of Islamic Cooperation (OIC) in promoting ceasefires, accountability, and victim recovery. The findings indicate that vetoes and material support create systemic barriers to compliance with humanitarian law, significantly weakening efforts to protect human rights. Nevertheless, Indonesia’s and the OIC’s consistent diplomacy contributes to mobilizing international support, although their policy leverage remains limited in the absence of concrete enforcement mechanisms. The main implication of this study underscores the urgent need for a stronger architecture of global compliance, including restrictions on arms support that prolong conflict, conditioning international aid on human rights compliance, ensuring humanitarian access, and reinforcing the implementation of rulings and provisional measures of international judicial bodies, in pursuit of effective accountability and human rights protection.